Browser security: threats, multi-factor authentication, and advanced protection mechanisms - Khyzhniak, M. А. (ХНУРЕ, 2025)
This work provides an overview of key cybersecurity threats related to web browsers and the role of multi-factor authentication (MFA) in enhancing security. It examines threats such as phishing attacks, malware, man-in-the-middle (MITM) attacks, and malicious browser extensions. Special attention is given to the development of MFA and its impact on browser security, with a focus on modern authentication standards like WebAuthn and FIDO2, highlighting their advantages over traditional security methods [1, 2] and the need for widespread implementation of MFA.
Keywords: Browser security; multi-factor authentication